Impact of Upper Eyelid Surgery on Symptom Severity and Frequency in Benign Essential Blepharospasm - Timlin, Hannah Mary (J Mov Disord, 2021)
OBJECTIVE: To assess the impact of periocular surgery, other than orbicularis stripping, on the severity and frequency of blepharospasm symptoms. METHODS: Consecutive patients with benign essential blepharospasm (BEB) who underwent eyelid/eyebrow surgery with the aim of improving symptoms were retrospectively reviewed over a 5-year period. Patients who had completed the Jankovic Rating Scale (JRS) and Blepharospasm Disability Index (BDI) pre- and at least 3 months postoperatively were included. RESULTS: Twenty-four patients were included. JRS scores significantly improved from 7.0 preoperatively to 4.1 postoperatively (p < 0.001), and BDI scores significantly improved from 18.4 preoperatively to 12.7 postoperatively (p < 0.001); the mean percentage improvements were 41% and 30%, respectively. Patients were followed for a median of 24 months postoperatively. CONCLUSION: Periocular surgery significantly reduced BEB symptoms in the majority (83%) of patients by an average of 33% and may therefore be offered for suitable patients. An important minority (17%) of patients experienced symptom worsening.